Hepatoprotector Edible Flower in Indonesia: A Review - Kresnapati, I Nyoman Bagus Aji; Kurniawan, Salsabila Yunita; Novitarini, Novitarini; Pratiwi, Baiq Yulia Hasni (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Hepatotoxicity is an agent that causes damage to human liver function, and every year, cases of liver damage are increasing. Agents that cause liver damage, such as drugs (Paracetamol), chemicals, Carbon Tetrachloride (CCL4), cause liver damage, which is characterized by an increase in the liver enzymes Serum Glutamic Oxaloacetic Transaminase (SGOT) and Serum Glutamic Pyruvic Transaminase (SGPT). Giving natural ingredients such as edible flower extracts (hepatoprotectors) can reduce SGOT and SGPT levels in liver damage (Hepatoxicity). Indonesia is a country rich in biodiversity, including edible flowers. Therefore, the purpose of this study was to analyze edible flowers that grow in Indonesia and have hepatoprotective activity. This research method is based on a Google Scholar search for the last 5 years (2024-2020) with a keyword search for herbal plants that grow in Indonesia, then selected edible flowers, and a search for edible flowers, then selected edible flowers that act as hepatoprotective. From the search results, edible flowers that act as hepatoprotectors were obtained, namely, Rosella Flower (Hibiscus sabdariffa), Pagoda Flower (Clerodendrum paniculatum L.), Water Hyacinth Flower (Eichhornia crassipes), French Marigold Flower (Tagetes Patula) and Butterfly Pea Flower (Clitoria ternatea), which grow abundantly in Indonesia. Based on the content of active edible compounds, namely flavonoids, anthocyanins, tannins, alkaloids, saponins, terpenoids, phenolic acids and carotenoids, with flavonoids being the most dominant found in all edible flowers. And among the 5 edible flowers as hepatoprotective, only 2 are the most familiar in Indonesia, namely Rosella Flower (Hibiscus sabdariffa) and Butterfly Pea Flower (Clitoria ternatea), so it can be concluded that the most familiar hepatoprotective edible flowers in Indonesia are Rosella Flower (Hibiscus sabdariffa) and Butterfly Pea Flower (Clitoria ternatea).